2019
DOI: 10.1007/s40617-019-00352-7
|View full text |Cite
|
Sign up to set email alerts
|

Rules and Statements of Reinforcer Loss in Differential Reinforcement of Other Behavior

Abstract: Providing a rule regarding consequences for behavior can increase the efficacy of differential reinforcement of other behavior (DRO) procedures in the treatment of severe problem behavior (Watts, Wilder, Gregory, Leon, and Ditzian, Journal of Applied Behavior Analysis, 46, 680-684, 2013). The purpose of the current study was to replicate and extend the literature on DRO procedures by evaluating the efficacy of rules and statements of reinforcer loss (SRL) in the treatment of severe problem behavior. Conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Omission training, also known as differential reinforcement of other behavior (DRO), is a schedule of reinforcement in which reinforcers are delivered contingent on the nonoccurrence of a target response (Reynolds, 1961). Omission is commonly used to treat a wide variety of problem behavior including substance abuse (e.g., contingency management and the therapeutic workplace; Higgins et al, 1991;Silverman et al, 1996), medical noncompliance (e.g., Cuvo, Reagan, Ackerlund, Huckfeldt, & Kelly, 2010;Shabani & Fisher, 2006;Slifer, Avis, & Frutchey, 2008), and problem behavior common in individuals with developmental and intellectual disabilities (e.g., aggression, self-injurious behavior, and disruption; Iannaccone, Hagopian, Javed, Borrero, & Zarcone, 2019). Omission is commonly used to treat a wide variety of problem behavior including substance abuse (e.g., contingency management and the therapeutic workplace; Higgins et al, 1991;Silverman et al, 1996), medical noncompliance (e.g., Cuvo, Reagan, Ackerlund, Huckfeldt, & Kelly, 2010;Shabani & Fisher, 2006;Slifer, Avis, & Frutchey, 2008), and problem behavior common in individuals with developmental and intellectual disabilities (e.g., aggression, self-injurious behavior, and disruption; Iannaccone, Hagopian, Javed, Borrero, & Zarcone, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Omission training, also known as differential reinforcement of other behavior (DRO), is a schedule of reinforcement in which reinforcers are delivered contingent on the nonoccurrence of a target response (Reynolds, 1961). Omission is commonly used to treat a wide variety of problem behavior including substance abuse (e.g., contingency management and the therapeutic workplace; Higgins et al, 1991;Silverman et al, 1996), medical noncompliance (e.g., Cuvo, Reagan, Ackerlund, Huckfeldt, & Kelly, 2010;Shabani & Fisher, 2006;Slifer, Avis, & Frutchey, 2008), and problem behavior common in individuals with developmental and intellectual disabilities (e.g., aggression, self-injurious behavior, and disruption; Iannaccone, Hagopian, Javed, Borrero, & Zarcone, 2019). Omission is commonly used to treat a wide variety of problem behavior including substance abuse (e.g., contingency management and the therapeutic workplace; Higgins et al, 1991;Silverman et al, 1996), medical noncompliance (e.g., Cuvo, Reagan, Ackerlund, Huckfeldt, & Kelly, 2010;Shabani & Fisher, 2006;Slifer, Avis, & Frutchey, 2008), and problem behavior common in individuals with developmental and intellectual disabilities (e.g., aggression, self-injurious behavior, and disruption; Iannaccone, Hagopian, Javed, Borrero, & Zarcone, 2019).…”
mentioning
confidence: 99%
“…During omission training, the organism must learn to withhold, or inhibit, the target response in order to receive reinforcement because reinforcers are delayed or omitted contingent on the occurrence of the target response. Omission is commonly used to treat a wide variety of problem behavior including substance abuse (e.g., contingency management and the therapeutic workplace; Higgins et al, 1991;Silverman et al, 1996), medical noncompliance (e.g., Cuvo, Reagan, Ackerlund, Huckfeldt, & Kelly, 2010;Shabani & Fisher, 2006;Slifer, Avis, & Frutchey, 2008), and problem behavior common in individuals with developmental and intellectual disabilities (e.g., aggression, self-injurious behavior, and disruption; Iannaccone, Hagopian, Javed, Borrero, & Zarcone, 2019). In addition to their common therapeutic use, omission schedules are abundant in everyday social interactions.…”
mentioning
confidence: 99%
“…However, practical and technological constraints may make such an analysis difficult. Responses were categorized to record instances of nontarget‐other responding—a strategy that has proven useful in related research (Iannaccone et al, 2019). However, it is possible that two different topographies of behavior that have different functions could have been recorded as the same behavior, therefore artificially increasing the frequency of a specified nontarget‐other response.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that fixed-time schedules of reinforcement have led to increases in an alternative response (Roane et al, 2001). Although several studies have directly measured other behavior while conducting DRO in an attempt to more closely examine the causal mechanism(s) of DRO (e.g., Iannaccone et al, 2019;Jessel et al, 2015;Leitenberg et al, 1977;Miller & Jones, 1997;Repp & Deitz, 1974;Rey et al, 2020a;Rey et al, 2020b;Thompson et al, 2003), these studies have obtained mixed results on whether other behavior increased during DRO. Jessel et al (2015) empirically evaluated the potential strengthening effects of a DRO procedure on other behavior.…”
mentioning
confidence: 99%
“…For this reason, a differential reinforcement of other behavior (DRO) contingency was also utilized with Billy. In a DRO, an interval of time is determined within which the absence or omission of a target response results in contingent reinforcement (Iannaccone et al, 2020). If the target behavior occurs within the time interval, the interval is reset and the process starts again.…”
Section: Case Conceptualizationmentioning
confidence: 99%